Mechanical, Thermal, and Sound Properties of Bamboo-Powder-Filled Polyurethane Composites - Yesilyurt, Aysenur; Parin, Fatma Nur; Uysal, Naci (Wiley-V C H Verlag Gmbh, 2024)
Bamboo, which is called green gold because of its sustainability characteristics, has many wonderful properties that make it environmentally friendly. In this study, polyurethane (PU) composites used in the automotive industry were produced by adding different amounts of bamboo powders (1, 2.5, 5, 7.5, 10 and 15%, w/v) to PU foams. In this regard, density, light and stereomicroscopic analysis, thermal conductivity, spectroscopic analysis, and mechanical (compression) test have been performed. Further, sound absorption analysis and contact angle analysis have been carried out. Optical and stereomicroscopes showed average pore sizes with range of 258-482 mu m. As the bamboo powder increased, the contact angle values decreased from 129 degrees to 88 degrees. Compression force deflection values of the samples declined from 1850 to 360 g/cm2. Similar to the mechanical properties, the thermal conductivities of the PU foams decreased. However, in regards to FT-IR, no chemical reactions were observed between PU matrix and bamboo powder. The sound absorption test results showed that bamboo powder filled PU foams are sound absorption materials and that rigid PU foam with 2.5% (w/v) (PU-2.5) bamboo powder sample had better sound absorption properties than the bamboo-powder-unfilled rigid PU foam (PU-0), with an average sound absorption coefficient value of 0.86 at 6300 Hz and 0.71 in the range of 1600-6300 Hz. Bamboo powder, called green gold, has been used in the production of polyurethane foams that are used in many sectors. Thermal conductivity, sound absorption, mechanical strength, wettability, pore size, and sponge apparent density properties of polyurethane foams were examined depending on the proportions of bamboo powder. In line with the data obtained, it has been observed that bamboo#x02010;powder#x02010;filled polyurethane foams can be used as sound insulation materials and thermal insulation materials. image
Keywords: Bamboo powder; Polyurethane; Porous foams; Sound property; Thermal conductivity